Effect of potassium on a model soot combustion: Raman and HRTEM evidences. Issue 4 (2nd April 2016) - Castoldi, L.; Matarrese, R.; Brambilla, L.; Serafini, A.; Tommasini, M.; Lietti, L.
ABSTRACT: The effect of potassium on the oxidation of a model carbonaceous material (Printex U, namely, soot for brevity) has been investigated under isothermal conditions. For this purpose, Raman spectroscopy, Transmission Electron Microscopy (TEM), and Brunaure, Emmet, Teller surface area characterization have been applied to investigate structural changes occurring during soot oxidation both in the presence and in the absence of potassium. The Raman spectra of the model soot during combustion showed that oxidation preferentially involves the amorphous carbon fraction of the soot and only subsequently it affects the more ordered sp 2 domains. However, in the K-doped Printex U the oxidation of both the amorphous and more ordered sp 2 structures occurs concurrently. These findings have been confirmed by TEM analysis and explain the observed higher combustion activity of K-containing sample. Copyright © 2016 American Association for Aerosol Research